Biodigestão anaeróbia da fração orgânica de resíduos sólidos urbanos - Schulz, Francine (Universidade do Vale do Rio dos Sinos, 2015)
The energy use of the organic fraction of municipal solid waste (MSW) for biogas generation is a viable alternative to minimize the social and environmental impacts caused by the accumulation and disposal of these wastes in the landfills. Anaerobic digestion, under controlled conditions, aims to maximize the yield and quality of the biogas produced. Among all the parameters monitored, pH, alkalinity, the concentration of volatile fatty acids and temperature are critical for the process optimization. The aim of this study was to determine the appropriate operational conditions for obtaining the best performance in the production of biogas, using as substrate the organic fraction rejected by the central operation of sorting from the landfill in São Leopoldo - RS. The experiment was performed in an anaerobic reactor of stainless steel with a volume of 50L, operated in batch with intermittent mixing. Before each batch the organic fraction of MSW was ground in a mechanical mill. Five batches were performed using diferent organic loading rates and different volumes of inoculum, in order to stabilize the pH of the system within the optimum range of the process and also increase the amount of biogas. As a result we have that the organic fraction of MSW demonstrated potential for degradation and biogas production (minimum of 6.71 and maximum of 22.45 m3 / ton MSW). The methane concentrations were between 70% and 80% at the end of the batches, even at acid pH (5.5-5.6). The difficulty of properly mix the samples collected may have influenced the results for TOC (Total Organic Carbon). The values of this variable increased over time, not coinciding with that found for the VS (Volatile Solids) levels that decreased over time. In all experimental batches was difficult to maintain the pH and the temperature within the optimum range process, this fact can explain the low production of biogas when compare to other studies. The organic loading rates, when considered alone as a variable, did not seemed to influence the final volume of biogas produced in the batches tested, but it did influence to balance and maintain the pH in the adequate range for the anaerobic digestion.
Anaerobic biodigestion of the organic fraction of municipal solid waste
Keywords: Biogás; Digestão anaeróbia; Resíduos sólidos urbanos; Biorreator; Biogas; Anaerobic digestion; Municipal solid waste; Biodigester; ACCNPQ::Engenharias::Engenharia Civil